Giardiasis in dogs under three years of age that go to public parks in the district of Santiago de Surco in Lima - Huamancayo L., Fiorela (2015)
The aim of this study was to estimate the frequency of infection by Giardia sp in dogs under three years of age that go to public parks in the district of Santiago de Surco, Lima, Peru, and to determine the concordance among three diagnostic techniques. Stool samples were collected from 140 apparently healthy dogs under 3 years old that went to public parks accompanied by their owners. For the diagnosis of the samples, three techniques were used: Chromatography Immune-essay (CIE), Faust’s technique (FT) and Spontaneous Sedimentation Technique (SST). The results showed that 25.0, 17.9 and 12.1% of dogs were infected with Giardia sp according to the three techniques respectively. Analysis of association between the frequency of infection and the predictor variables (sex, age, physical status of the stools, number of daily visits to the park) in a logistic regression model did not show statistical significance. The Kappa indexes of concordance among the three diagnostic tests were 0.78 (CIE vs FT), 0.58 (CIE vs SST) and 0.77 (FT vs SST) (p<0.05). The results showed a moderate level of infection with Giardia sp indicating a potential of zoonotic risk to human population. In addition, both IEC and TF techniques showed a substantial levels of of concordance.